Eco-ethology of the common langur Semnopithecus entellus (Dufresne) in Bangladesh - Ahsan, M Farid; Khan, MA Reza (University Journal of Zoology, Rajshahi University, 2007)
Eco-ethological aspects of the common langur (Hanuman) Semnopithecus entellus (Dufresne) were studied between July and September 1981 in the rural areas of Keshabpur Police Station, Jessore, Bangladesh. Three bisexual troops were monitored for 355 hrs for determining group-size and composition, age-sex relationship, and other ecological and behavioural features. The average group-size was 13.67±0.00 in July and 14.67±1.33 in September. Of the major diurnal activities viz., rest, move, sit, social groom, self groom, play and feed, the Hanumans spent maximum time in sitting (44.32%). Dyad behaviour of the Hanumans and their relationships with other animals including man has been described. Hanumans used more than 60 species as food plants of which 43 were identified. They mostly ate vegetative plant parts (74.88%), thus indicating their folivorous nature. The welfare of the Hanumans has also been dealt with. Key words: Common langur (Hanuman), Semnopithecus entellus, ecology, ethology, Bangladesh Univ. j. zool. Rajshahi Univ. Vol.25 2006 p.3-10